Structural diversity in the products formed by the reactions of 2-arylselanyl pyridine derivatives and dihalogens. (22nd March 2018) - Montis, Riccardo; Arca, Massimiliano; Aragoni, M. Carla; Blake, Alexander J.; Castellano, Carlo; Demartin, Francesco; Isaia, Francesco; Lippolis, Vito; Pintus, Anna; Lenardão, Eder J.; Perin, Gelson; O'Connor, Alice E.; et al.
Abstract : The presence of competing donor sites inL1–L4 influences their reactivity towards dihalogens and interhalogens. Abstract : The reactivity of the 2-arylselanyl pyridine derivativesL1–L4 towards dihalogens X2 (X = I, Br) and interhalogens IX (X = Cl, Br) was studied in CHCl3 or CH3 CN. The solid products obtained were structurally characterized and their nature points out the preference for CT spoke adducts and for seesaw insertion adducts to be formed at the N-donor and Se-donor site, respectively. DFT calculations were performed to provide a rationale for the structural diversity observed in the products obtained.